2012
DOI: 10.1007/s00428-012-1218-y
|View full text |Cite
|
Sign up to set email alerts
|

Urinary bladder chondroma

Abstract: Dear Editor, Soft tissue chondromas are rare tumors that most often occur in the fingers, less commonly in the hands and feet, and rarely in other areas of the body [1]. There has been one previously reported extraskeletal chondroma of the urinary bladder, which occurred in a patient with no prior urologic history [2].A 62-year-old female presented with dysuria, frequency, nocturia, lower abdominal pain, and constipation that had been worsening over the past 4 years. Cystoscopy showed patchy inflammation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Only two prior cases of chondroma of the urinary bladder wall have been reported. 1,2 The most common mesenchymal tumours of the bladder are leiomyomas, leiomyosarcomas, and pleomorphic undifferentiated sarcomas (formerly malignant fibrous histiocytoma). 3 In recent years there have also been at least 8 reported cases of perivascular epithelioid cell tumour (PEComa) of the bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only two prior cases of chondroma of the urinary bladder wall have been reported. 1,2 The most common mesenchymal tumours of the bladder are leiomyomas, leiomyosarcomas, and pleomorphic undifferentiated sarcomas (formerly malignant fibrous histiocytoma). 3 In recent years there have also been at least 8 reported cases of perivascular epithelioid cell tumour (PEComa) of the bladder.…”
Section: Discussionmentioning
confidence: 99%
“…The other bladder chondroma, however, was identified in a woman with a concomitant minimally invasive high-grade urothelial carcinoma of the bladder and symptoms of dysuria, frequency, nocturia, lower abdominal pain, and constipation. 1 It is not possible to know what role, if any, the coexisting urothelial carcinoma played in the development of the latter patient's chondroma. A connection between these two lesions seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…They are rare, except of those arising in the hands and feet of middle-aged adults [1] . A literature review revealed only eight extraosseous chondromas in the pelvic region, six of them in females [2][3][4][5][6][7][8][9] . Two of these cases were reported in the urinary bladder, in 62 and 63 year-old patients with submucosal solid masses, composed of mature cartilage [2][3] .…”
Section: Discussionmentioning
confidence: 99%
“…Two of these cases were reported in the urinary bladder, in 62 and 63 year-old patients with submucosal solid masses, composed of mature cartilage [2][3] . Three young patients had fallopian tube lesions; a 32 year-old patient, 30 year-old woman with 3cm×2 cm nodular mass noted on the left tubal serosal area, a 31 year-old patient with 1.6 cm subserosal nodule detected in an elective tubal ligation; contralateral tube was normal [4][5][6] . In Brazil, an 11-year-old girl was referred for a painless solid tumor located on the mons pubis that was diagnosed as chondroma that could be considered a case of chondroma cutis [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation